Manifestations of Three-Sector Economy Model in Countries with Transition Economies (on the example of RA). - Nersisyan, Armen (Bulletin of Yerevan University G: Economics, 2018)
The article examines the application possibilities of Colin Clark’s three-sector economy theory in the countries with transition economies. Based on the analysis of statistical data, it is proved that for countries with economies in transition, only the analysis of the sector structure of the economy is not sufficient to conclude which type of country it belongs to. From this perspective, the need to study the services sector is based on the priorities of the knowledge based groups.